Full-dimensional MCTDH/MGPF study of the ground and lowest lying vibrational states of the bihydroxide H3O-2 complex - Peláez, Daniel; Sadri, Keyvan; Meyer, Hans-Dieter (Spectrochimica acta. A, Molecular and biomolecular spectroscopy, 2014)
In this study, we present a full-dimensional (9D) quantum dynamical analysis of the lowest vibrational eigenstates of H3O2-. We have made use of the Multiconfiguration Time-Dependent Hartree method in conjunction with both an analytical and a numerical representation of the Kinetic Energy Operator and the newly developed Multigrid POTFIT [D. Peláez, H.-D. Meyer, J. Chem. Phys. 138 (2013) 014108], an algorithm which performs the transformation of a high-dimensional (up to ∼12D) Potential Energy tensor into product form. Many sets of top-down Multigrid POTFIT expansions, differing in the system coordinate definition (valence and Jacobi), as well as in the number of terms in the expansion, have been analyzed. Relaxations for the computation of the ground states energies have been carried out on these potentials, obtaining an excellent overall agreement with accurate previous Diffusion Monte Carlo (DMC) calculations, irrespective of the coordinate choice. The 24 lowest excited vibrational states of H3O2- have been computed by Block Relaxation and assigned for the first time. This has been carried out in two different pictures, namely: a 7D reduced dimensional one, in which the OH distances have been frozen at the Potential Energy Surface minimum, and a 9D full-dimensional one. The agreement between both descriptions is remarkable. The following fundamental modes have been characterized: OH torsion, OO stretching, OH wagging, OH rocking, and the elusive bridging H stretching. In particular, we provide a very accurate description of the latter in perfect agreement with experiment.
Online 21 May 2013
Im Text ist "-" hochgestellt, "3" und "2" tiefgestellt
Gesehen am 06.10.2020